Examination of the effect of aging process on marginal fit and fractute strength of temporary crowns prepared from different materials - Bahriye Bahar Tüfekçi; Zeynep Yeşil (Heliyon, 2024)
Aim: The aim of this study is to investigate the effect of the aging process on the marginal fit and fracture resistance of temporary crowns prepared using different materials. Materials and method: The steel die to represent the maxillary first premolar used in this study was produced on a CNC turning machine to include an anatomical occlusal surface. A total of 160 epoxy resin dies were obtained by taking impressions with conventional impression methods on the metal die. Epoxy resin dies were randomly divided into four groups. Temporary crowns were prepared for each group from poly acrylic resin (Vita CADTemp®), bis-acryl composite resin (Protemp 4), poly methyl methacrylate (PMMA; Imident) and poly ethyl methacrylate (PEMA; Dentalon Plus) restorative materials. Half of the specimens (n = 20) in each group (n = 40) were randomly separated and the aging process was applied 5000 times in the device. Marginal gap measurements on epoxy resin dies were made using a stereomicroscope. The fracture strength test of the specimens was performed by using the Instron Universal Test Device. Jamovi 2.2.5 statistical program was used for statistical analysis. Results: When compared to temporary crowns prepared from all other materials, poly acrylic resin (Vita CADTemp ®) temporary crowns observed significantly lower marginal gap values (59,05 μm) regardless of the aging process, and a significantly higher fracture resistance (478,44 N) in the presence of aging process (p < .05 for each). While the highest marginal gap value was detected in PMMA (Imident) (120.36 μm) temporary crowns with aging process, the lowest marginal gap value was observed in poly acrylic resin (Vita CADTemp®) (59.05 μm) crowns without non-aging process. The marginal fit and fracture resistance of all temporary crowns were negatively affected by the aging process. Conclusion: Our findings revealed the superiority of poly acrylic resin (Vita CADTemp®) crowns to the temporary crowns prepared from all other materials in terms of the significantly lower marginal gap in the absence of aging process, and the significantly higher fracture resistance in the presence of aging process. Marginal fit and fracture resistance values for all materials were found to be within clinically acceptable limits.